2001
DOI: 10.1002/per.407
|View full text |Cite
|
Sign up to set email alerts
|

Different personality patterns in non‐socialized (juvenile delinquents) and socialized (air force pilot recruits) sensation seekers

Abstract: Young delinquents are known to be sensation seekers. Not all sensation seekers become delinquents: many engage in socially accepted activities, such as mountaineering or parachute jumping. The present study compares 47 juvenile delinquents (mean age 17 years) with 18 Swedish air force pilot recruits (mean age 23 years) and 19 conscripts (mean age 18 years) as a control group. Sensation‐seeking behaviour, impulsiveness, and psychiatric/psychological vulnerability were measured by the Zuckerman Sensation‐Seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Another explanation might be that the military personnel are more sensation seeking and participate in activities with a higher risk of experiencing life-threatening events [49]. To our knowledge, few have compared the prevalence of life-threatening events between civilians and military personnel within the same organization.…”
Section: Discussionmentioning
confidence: 98%
“…Another explanation might be that the military personnel are more sensation seeking and participate in activities with a higher risk of experiencing life-threatening events [49]. To our knowledge, few have compared the prevalence of life-threatening events between civilians and military personnel within the same organization.…”
Section: Discussionmentioning
confidence: 98%
“…An example of such research is the work by Gibson and Cook (1996) that links neuroticism to inherited emotional lability of the autonomic nervous system. Further examples are research by Davidson, Jackson and Kalin (2000) and Tomarken, Davidson and Henriques (1990) who linked activation of the right frontal lobe to negative affect such as depression and anxiety, inhibition and avoidance behaviour, whereas activation of the left frontal lobe facilitates positive emotionality such as happiness, joyfulness and approach behaviour; research by Daderman, Meurling and Hallman (2001), Wills, Sandy, Yaeger and Shinar (2001) and Zuckerman, Buchsbaum and Murphy (1980) who showed that sensation seeking, extraversion and impulsivity can be linked to low levels of monoamine oxidase (MAO) in the blood platelets; and research by Zuckerman (1991) who showed that hormonal factors may affect aggression and hostility as well as general levels of activity. Zuckerman's (1991) five factors have been referred to as 'The Alternative Five' to distinguish them from 'The Big Five' personality factors (Costa & McCrae, 2001) and describe individual differences in behaviour in a stressful situation (Vollrath, 2001).…”
Section: Temperamentmentioning
confidence: 97%
“…Despite a high prevalence of impulsivity among adolescent offenders (e.g., Daderman, 1999;Daderman et al, 2001;Luengo, Otero, Carrillo-de-la-Pena, & Miron, 1994), and a number of studies documenting a strong association between impulsive traits and HIV risk behavior in adults (Kelly, 1997;McCoul & C Haslam, 2001), relatively little attention has been focused on these relationships among incarcerated adolescents. This study confirms the existence of a relationship between impulsivity and a variety of HIV-risk related attitudes and behaviors even within a sample of adolescent offenders who might not have been expected to manifest a wide range of variability in impulsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…If the most impulsive incarcerated youth also report high-risk behaviors and negative attitudes, this may signal the need to identify such youth for special intervention programs designed to meet their needs. Furthermore, such findings within a population of individuals expected to be more impulsive and at-risk than average (e.g., Daderman, Wirsen Meurling, & Hallman, 2001;DiClemente, Lanier, Horan, & Lodico, 1991) will have implications for nonincarcerated adolescents at greater risk of contracting HIV/AIDS due to their at-risk behaviors.…”
mentioning
confidence: 99%